The Attribution of the Children’s Book Publishing Statistics in Ukraine in the Second Half of the 19th and Beginning of the 20th Centuries - Petrenko, Oksana (Knygotyra, 2020)
This article sheds light on the first research attempt to establish the bibliographic and statistical accounting of the books that were published in Ukraine in the 19th century. Besides, the article has analysed the beginning of the institutionalization of the children’s books’ publishing statistics in Ukraine. The author seeks to answer the question of who was at the origin of the formation of the children’s books’ publishing statistics. Library and museum funds became reliable sources of attribution of the children’s books’ publishing statistics in Ukraine. The results of received data on old-printed children’s books have been studied, systematised and compared with the data of other old-printed books that were found in other library collections. According to this, there is the conclusion about the primacy or repetition in the bibliographies of old-printed children’s books that became the basis for creating a summary table. This article offers insights into the chronology of publishing children’s books in Ukraine from the beginning of their publishing to the start of the state registration of publications.